The Effect of Financial Condition on Firm Value: A Comparative Study - Nugroho, Dwiyanjana Santyo (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021)DO - 10.24843/JIAB.2021.v16.i02.p02, 2021)
This study analyzes a company’s financial condition on firm value. We also evaluated the difference in firm value between corporate sectors affected and unaffected by the COVID-19 pandemic. The regression analysis model used is the random effect model as well as the difference-in-difference technique. The study uses data from the company’s interim financial reports for the first and second quarters of 2018, 2019, and 2020. We found that firm size and leverage influence firm values. This applies to companies in the affected sectors, such as hotel, restaurant, and tourism sub-sectors, and unaffected sectors, such as health, pharmacy, and telecommunication sub-sectors. We also found that firm values in affected and unaffected sectors, before and during COVID-19, do not significantly differ.